IMPLEMENTASI PENDIDIKAN KESEHATAN DENGAN METODE BRAINSTORMING TERHADAP PENGETAHUAN REMAJA TENTANG TUMBUH KEMBANG DI PAUH KOTA PADANG - Busrini Hartati; Rika Sarfika; Dewi Eka Putri (Jurnal Hilirisasi IPTEKS, 2019)
Teenagers are the next generation of the nation that must be guarded in order to continue the struggle and realize the ideals of the nation. Adolescence is a turbulent period, during which time conflicts easily occur due to drastic growth and development. Teenagers who experience failure in developing their sense of identity will cause loss of direction and experience confusion of roles that can have an impact on deviant behavior, such as closing themselves from the community, taking actions that are criminal or brawl so that they are not rarely seen by the environment as deviations or delinquency. As a preventive effort, community service activities are carried out in the form of providing health education about growth in adolescents. The venue for the activity was in the village of Cupak Tangang, Pauh District, Padang City. The number of participants was 34 teenagers aged 12-18 years and had normal growth and development. The health education method uses brainstorming techniques and group discussions with the IV pillar CHMN (Community Mental Health Nursing) approach, case management. The measuring instrument uses a questionnaire of 11 questions in the form of self-reported which describes the teenager's knowledge of growth and development experienced. The results of the activity found that there was an increase in knowledge that was used in adolescents about growth before and after being given health education (p <0.05). The level of knowledge of adolescents before being given health education on average 6 and after being given health education on average increases to 10. Suggestions for parents to be able to stimulate growth in adolescents by way of providing democratic and permissive parenting. It is expected that CMHN nurses who are in the health center can continue health education on an ongoing basis as a preventive effort to prevent deviant behavior in adolescent.